Longer Plate-to-Disc Distance Prevents Adjacent-Level Ossification Development But Does Not Influence Adjacent-Segment Degeneration. Issue 7 (1st April 2015) - Yang, Haisong; Lu, Xuhua; He, Hailong; Yuan, Wen; Wang, Xinwei; Liao, Xinyuan; Chen, Deyu
<x xml:space="preserve">Abstract</x> Study Design. Retrospective case-control study. Objective. To clarify the association between plate-to-disc distance (PDD) and adjacent-level ossification development (ALOD) and adjacent segment degeneration (ASD). Summary of Background Data. Anterior cervical discectomy and fusion with plating provides higher fusion rate and improved alignment but has been reported to result in ALOD and ASD. Methods. We retrospectively reviewed 218 patients with solid fusion after anterior cervical arthrodesis with plating at our institution between January 2004 and December 2010. PDD was measured on postoperative lateral radiographs for each adjacent disc space and used to assign patients to 1 of 3 groups: group L, long PDD (>5 mm); group S, short PDD (0 mm ⩽PDD ⩽5 mm); and group N, PDD (<0 mm, disk space encroachment). Mean follow-up was 5.3 years. Incidences of cranial and caudal ALOD and ASD with and without symptoms were compared among groups. Severity of caudal ossification was not measured in 30 patients because bony overlap precluded adequate visualization of the caudal level. Results. Ossification developed in 134 (61%) of 218 cranial adjacent disc spaces and 45 (24%) of 188 caudal adjacent disc spaces (P < 0.01). Mean cranial PDD was shorter than mean caudal PDD (P < 0.01). Ossification rate was higher in group N than in group S at the cranial adjacent disc spaces (100% vs. 66%, P < 0.01). Incidences of both cranial and caudal ALOD were significantly higher in group S than in group L (66% vs. 31%, P < 0.01; and 31% vs. 13%, P < 0.01, respectively). No significant differences in symptomatic and asymptomatic ASD were seen among groups. Conclusion. Longer PDD does not decrease the incidence of ASD but it can prevent ALOD. We now attempt to place anterior cervical plates of 5 mm or greater from adjacent disc spaces. Level of Evidence: 3